Synthesis of cyclopentane amide DNA (cpa-DNA) and its pairing properties - Ahn, DR; Mosimann, M; Leumann, CJ (AMER CHEMICAL SOC, 2003)
We recently reported on the synthesis and pairing properties of the DNA analogue bicyclo[3.2.1]-amide DNA (bca-DNA). In this analogue the nucleobases are attached via a linear, 4-bond amide-linker to a structurally preorganized sugar-phosphate backbone unit. To define the importance of the degree of structural rigidity of the bca-backbone unit on the pairing properties, we designed the structurally simpler cyclopentane amide DNA (cpa-DNA), in which the bicyclo[3.2.1]-scaffold was reduced to a cyclopentane unit while the base-linker was left unchanged. Here we present a synthetic route to the enantiomerically pure cpa-DNA monomers and the corresponding phosphoramidites containing the bases A and T, starting from a known, achiral precursor in 9 and 12 steps, respectively. Fully modified oligodeoxynucleotides were synthesized by standard solid-phase oligonucleotide chemistry, and their base-pairing properties with complementary oligonucleotides of the DNA-, RNA-, bca-DNA-, and cpa-DNA-backbones were assessed by UV melting curves and CD-spectroscopic methods. We found that cpa-oligoadenylates form duplexes with complementary DNA that are less stable by -2.7 degreesC/mod. compared to DNA. The corresponding cpa-oligothymidylates do not participate in complementary base-pairing with any of the investigated backbone systems except with its own (homo-duplex). As its congener bca-DNA, cpa-DNA seems to prefer left-handed helical duplex structures with DNA or with itself as indicated by the CD spectra.
Keywords: CHIRAL ACYCLIC ANALOGS; OLIGONUCLEOTIDES; RECOGNITION; PRINCIPLES; BACKBONE